2013
DOI: 10.1186/1865-1380-6-34
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the community first responder system into Japan: is that possible?

Abstract: BackgroundTo improve out-of-hospital cardiac arrest (OHCA) survival rates in Japan, implementation of a community first responder (CFR) system is considered one of the most effective emergency medical service options. We investigated the possibility of introducing a CFR system in Japan.MethodsCross-sectional surveys were given to 1,350 residents over the age of 18 who were selected from resident registration lists in Tochigi prefecture. Residents were questioned whether they would agree to have a CFR system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Before starting a volunteer or CFR program, the possibility of the introduction of such a program needs to be investigated, and for this purpose, pilot programs and surveys can be used. Such an investigation in Tochigi prefecture, Japan, indicated that, by providing information to society and the required infrastructural elements, it is possible that a CFR system can be successfully introduced and operated in Japan (Toyokuni et al, 2013). Focusing on a volunteer program for OHCA cases in the Netherlands, Scholten et al (2011) found several potential focus points, including the alerting process and technical adjustments, to improve the system.…”
Section: Effective Utilization Of Volunteersmentioning
confidence: 99%
“…Before starting a volunteer or CFR program, the possibility of the introduction of such a program needs to be investigated, and for this purpose, pilot programs and surveys can be used. Such an investigation in Tochigi prefecture, Japan, indicated that, by providing information to society and the required infrastructural elements, it is possible that a CFR system can be successfully introduced and operated in Japan (Toyokuni et al, 2013). Focusing on a volunteer program for OHCA cases in the Netherlands, Scholten et al (2011) found several potential focus points, including the alerting process and technical adjustments, to improve the system.…”
Section: Effective Utilization Of Volunteersmentioning
confidence: 99%